From Socialism to Open Cooperativism: Convergences and Divergences in the Work of Castoriadis, Olin Wright and Bauwens (Global Journal of Human-Social Science, 2018)
This article attempts at integrating core socialist elements analyzed through the prism of Castoriadis s and Wright s work into a model of open cooperativism between Commons-based peer production ethical market entities and a partner state introduced by Bauwens and Kostakis It concludes with a critical appraisal of Bauwens and Kostakis s model
Keywords: socialism; castoriadis; wright; bauwens and kostakis; open cooperativism